IMPACT OF ELIMINATION OF AUTOMATIC DETENTION OF COCOA PRODUCTION INDONESIA - Arum Putranti; Joni Murti Mulyo Aji (UNEJ e-Proceeding, 2012)
Increased export volume of Indonesian cocoa exports could open up opportunities and make Indonesia a leading producer of cocoa. The Government expects the exporters began to seek opportunities to export processed cocoa cocoa commodity export prices to rise. The volume of cocoa in the cocoa trade in Indonesia is affected either directly or indirectly. Based on the conditions that have been described in the background of the above problems, it is necessary to study about the impact of Automatic Detention of Indonesian cocoa production.